Political booms local money and power in Taiwan, East China, Thailand, and the Philippines - White, Lynn T. (Series on Contemporary China, 2009)
Why have Taiwan, rich parts of China, and Thailand boomed famously, while the Philippines has long remained stagnant both economically and politically? Do booms abet democracy? Does the rise of middle "classes" promise future liberalization? Why has Philippine democracy brought no boom and barely served the Filipino people?